High-throughput synthesis and evaluation of metal and metal oxide precursor films for two-step conversion to MoSe2 - Brian M. Everhart; Drake R. Austin; Mark Anayee; Mike A. Altvater; Benjamin M. Robertson; Matthew Kleyn; Liz Josephson; Mike Simmons; Arthur R. Woll; Peter R. Stevenson; Kurt Eyink; Michael R. Snure; et al. (npj 2D Materials and Applications)
Abstract Two-step conversion is a promising approach to produce high-quality films of two-dimensional (2D) transition metal dichalcogenides (TMD) from thin metal films. However, the influence of the intermediate metal oxide properties such as oxidation state, stoichiometry, structure, orientation, crystallinity, grain size, and defect density, on the resulting TMD properties have not been well-studied, in part because of the large processing parameter space. Herein, we studied the influence of laser annealing power and scan speed on the structure and chemistry of the metal and metal oxide films, and by extension, on the resulting TMD film. High-throughput processing of a 10 × 11 array on Mo thin films spanning the two processing parameters, complemented with diffraction, Raman, XPS, and ellipsometric mapping allowed us to efficiently optimize the synthesis of MoSe2. Amorphous, sub-stoichiometric (MoO2) resulted in the best in-plane (002) aligned MoSe2 films, which exhibited the highest refractive index >5, comparable to that observed in mechanically exfoliated material and films synthesized through molecular beam epitaxy.